Jack London's "Martin Eden" : Not everything you aspire to can be truly yours (Journal of Science-Innovative Research in Uzbekistan, 2023)
Jack London is one of the great writers of all time. There is no booklover who has not read his books. The novels written by him attract people from all over the world. Especially his "Martin Eden" deserves special attention. This book is still a lantern for dried up souls, as it motivates to act